ANALISIS PENGELOLAAN DANA DESA DALAM UPAYA MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA KUALA KARANG - Irwan, Nanang; Aminuyati, Aminuyati; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study entitled the analysis of Village Fund Management in an Effort to Improve the Community Economy of Kuala Karang Village, Teluk Pakedai District, Kubu Raya Regency is a qualitative research. Data collection techniques in this study used observation, interview, and documentation study techniques. Data collection tools used are interview guides, observation guides, notebooks and archives. The results showed that 1) the Village Fund Development Program which involved the community did not participate in the Village development program only involved a portion of the community that could be associated with the development program Community development planning that was promoted for the time being had not been done before conservation. 2) The implementation process of Village Fund Management has not been carried out to the maximum. Physical infrastructure such as infrastructure and transportation infrastructure have been implemented well as the construction of roads and bridges as transportation access, the implementation of community economic development has also not been carried out properly if there is an agriculture and fisheries sector that has not been approved. 3) The accountability of Village Fund Management is quite good form of accountability from the Village government in the form of Village Fund reporting has been conveyed to several parties both to the Regency / City Government and the communityÂ Keywords : Village Community Economy, Village Fund Management